The semantic extensions of Japanese onomatopoeias: verbal and pictorial metaphors - Domingues dos Santos, Silvio (2024)
The present article aims to present an overview of Japanese onomatopoeia, very common in japanese mangas, as well as the analysis of their semantic extensions arising via conceptual metaphor (Lakoff and Johnson,1980). Tomoda (1984) demonstrated some abstract features that onomatopoeias may manifest in certain discursive-verbal contexts; however, we assume that in addition to the mode mentioned, pictorial metaphor plays a fundamental role on semantic content enrichment. In such a process there are a verbal text and a term invoked pictorially through the context, thus providing a reinterpretation of that verbal text.